Stripe rust reaction and yield response of winter cereals in bio - versus conventional farming - Csősz, Lászlóné; Fónad, Péter; Óvári, Judit; Falusi, János; Petróczi, István; Bóna, Lajos; Matuz, János; Purnhauser, László; Pauk, János; Cseuz, László (Acta Agraria Debreceniensis, 2014)
In 2014, was an extremely early and heavy yellow rust (Puccinia striiformis var. striiformis) epidemic in Hungary. Significant differences were among locations, years and genotypes in the severity of infection. Ratio of the resistant and moderately resistant genotypes was higher under bio environment. The yellow rust epidemic caused significant yield decreasing in the tested winter cereals.